Integrasi Multimodal dalam Model Flipped Classroom untuk Pembelajaran Menulis Teks Eksplanasi: Multimodal Integration in the Flipped Classroom Model for Teaching Explanatory Writing - Asmayanti, Astri; Yudianda, Elvan (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2026)
This study aims to develop and produce a product in the form of multimodal integration in the flipped classroom model used in learning to write explanatory texts that is considered feasible by experts and users. This study uses a research and development (R&D) method with five main stages in the development process. To obtain comprehensive results, this study involved several participants consisting of 5 learning model experts, 6 learning media experts, 5 learning evaluation experts, 6 teachers, and 60 high school students in Bandung Regency. The research data were analyzed using descriptive quantitative and qualitative approaches. The results of the analysis show that the multimodal-based flipped classroom model received very good assessments from the validators, reviewed from the aspects of the model, media, and learning evaluation. Teachers gave positive responses that this model is effective, interesting, easy to implement, and has a positive influence on the learning process. Meanwhile, the results of student responses also showed interest, ease, and high influence on the application of the model. Based on these results, multimodal integration in the flipped classroom model is declared feasible to be applied in learning to write explanatory texts at the high school level.